Complement-Mediated Hemolytic Uremic Syndrome Due to MCP/CD46 Mutation: A Case Report - Abdul Muhsen Abdeen MD; Jowan Al-Nusair MD; Malik Samardali MD; Mohamed Alshal MD; Amro Al-Astal MD; Zeid Khitan MD (Journal of Investigative Medicine High Impact Case Reports)
Thrombotic microangiopathy (TMA) is a severe condition characterized by microangiopathic hemolytic anemia, thrombocytopenia, and end-organ damage, often involving the kidneys. Complement-mediated hemolytic uremic syndrome (cHUS), a rare form of TMA, arises from dysregulated alternative complement pathway activation, frequently due to genetic mutations. We report the case of a 23-year-old male presenting with TMA secondary to a heterozygous mutation in the membrane cofactor protein (MCP/CD46) gene. The patient exhibited severe renal and cardiovascular complications, including acute kidney injury requiring hemodialysis, uremic pericarditis, and persistent anemia. Diagnostic evaluation confirmed complement dysregulation, and management with eculizumab, plasmapheresis, and hemodialysis was initiated. Renal biopsy revealed classic TMA features, and genetic testing identified the MCP mutation, underscoring the importance of genetic predispositions in guiding diagnosis and therapy. This case emphasizes the critical role of genetic testing in TMA evaluation and highlights the potential for improved outcomes through targeted complement inhibition and individualized care strategies.